Last in a long line of rebels - Tyre, Lisa Lewis (New York, NY : Nancy Paulsen Books, An Imprint of Penguin Group (USA), 2015)
When the city of Zollicoffer, Tennessee, where her family lives, announces plans to seize their one hundred seventy-five year old house through eminent domain, twelve-year-old Louise Mayhew needs to come up with a way to save it--and her ancestor's Civil War diary linking the house to the Underground Railroad, as well as a hidden treasure, seem to offer her family the best chance of saving their home.
660
Q
Keywords: Underground Railroad -- Tennessee -- Juvenile fiction; Eminent domain -- Juvenile fiction; Historic buildings -- Juvenile fiction; Families -- Tennessee -- Juvenile fiction; Diaries -- Juvenile fiction; Treasure troves -- Juvenile fiction; Underground Railroad -- Fiction; Eminent domain -- Fiction; Historic buildings -- Fiction; Family life -- Tennessee -- Fiction; Diaries -- Fiction; Buried treasure -- Fiction; Tennessee -- Juvenile fiction; Tennessee -- Fiction